A descriptive analysis of anglicism in Ecuadorean magazines - Barrionuevo Villacrés, Jeaneth Alexandra (2012)
This study is based on a descriptive analysis of anglicisms in Ecuadorian Magazines. Its main purpose is to carry out a descriptive and linguistic analysis of present day written Spanish language focusing on lexical terms regarded as anglicisms. This investigation took place in Cuenca. In undertaking this research we analyzed three different types of magazines: two Cultural Magazines, two Scholarly Magazines, and two General Interest Magazines. The information was collected by reading and note-taking through use of cards and various other collection formats, and presented in tables and summary conclusions. The general approach of this study was both Qualitative and Quantitative; therefore, the qualitative method was used to the linguistic analysis that included syntactic - semantic and morphological analysis from ten selected anglicisms. In adittion, the quantitative method was used to determine the variable in which the anglicisms were most used and which were the most frequent in the researched magazines. In this research we found out the General interest magazines have the highest number of anglicisms because their variety of articles included topics in which anglicisms are necessary to use them, to explain that American culture is closely connected.